Effect of postmortem aging time on flavor profile of stewed pork rib broth - Miaomiao Hou; Dongmei Liu; Xinglian Xu; Guanghong Zhou; Chunbao Li (International Journal of Food Properties, 2018)
The objective of this study was to investigate changes in flavor components in broth prepared by pork ribs that were aged for 1 d, 3 d, and 7 d. The contents of free amino acids (FAAs), nucleic acid-related compounds, organic acids, and volatile compounds in broth were measured. The overall taste and aroma profiles were evaluated by electronic tongue, electronic nose, and sensory panelists. The results showed that the FAAs and succinic acid contents increased, while the 5ʹ-guanosine monophosphate, 5ʹ-inosine monophosphate, and 5ʹ-adenosine monophosphate contents decreased as the aging time increased. These changes led to the taste characteristics of broth being more savory. However, the results of gas chromatography-mass spectrometry, electronic nose, and sensory test all showed that there were no significant differences in aroma among the samples, where the main volatile compounds of broth were aldehydes, including hexanal, nonanal, octanal, heptanal, (Z)-2-heptanal, and (E)-2-decenal. Hence, postmortem aging affected the taste rather than the aroma of pork rib broth, and extending aging time can improve the taste of broth.